Pelatihan Dasar Gestur Dirigen bagi Pelayan Musik Jemaat Rehobot untuk Mendukung Kelancaran Liturgi Gereja - Cosye M. Sahureka; Aris Bidang; Cerry Fressly Nanuru; Deysi Mulder; Gusti Nyoman Pardomuan (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Music ministers play a crucial role in supporting the orderliness of church liturgy. However, not all music ministers possess adequate basic conducting skills, resulting in frequent rhythmic and coordination asymmetries between ministers. This community service activity aims to improve the skills of Rehobot Congregation's music ministers in understanding and instilling basic conducting gestures. The methods used included field observation, theoretical training, reflection, hands-on practice, and evaluation. The results showed significant improvements in participants' skills related to striking patterns, cueing, and coordination with the organist and choir. This training impacted the smoothness of liturgical music and improved the overall quality of worship services.